2011
DOI: 10.1063/1.3540409
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed eddy current differential probe to detect the defects in a stainless steel pipe

Abstract: Pulsed eddy current (PEC) is an electromagnetic nondestructive technique widely used to detect and quantify the flaws in conducting materials. In the present study a differential Hall-sensor probe which is used in the PEC system has been fabricated for the detection of defects in stainless steel pipelines. The differential probe has an exciting coil with two Hall-sensors. A stainless steel test sample with electrical discharge machining (EDM) notches under different depths of 1–5 mm was made and the sample was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The study of Ahmad et al [21] showed that pipes were frequently embedded in the soil with insulated coatings. Angani et al [22] studied the use of eddy current to inspect the defects in pipelines but the inspection can be carried out in a limited area only. It is impractical to use inspection methods that require direct access to the pipes since the associated cost of removing the insulation is unpredictably high.…”
Section: Damage Detection In Circular Waveguidesmentioning
confidence: 99%
“…The study of Ahmad et al [21] showed that pipes were frequently embedded in the soil with insulated coatings. Angani et al [22] studied the use of eddy current to inspect the defects in pipelines but the inspection can be carried out in a limited area only. It is impractical to use inspection methods that require direct access to the pipes since the associated cost of removing the insulation is unpredictably high.…”
Section: Damage Detection In Circular Waveguidesmentioning
confidence: 99%
“…The induced circumferential current is disturbed by a surface defect [17,18] on the surface of the pipe string, which makes the space magnetic field distorted. By measuring the distorted space magnetic field, the defect can be identified and evaluated [19,20] : …”
Section: Introductionmentioning
confidence: 99%
“…When underground pipes are damaged, they can lead to major financial losses and may cause loss of life. Various techniques have been developed for underground pipe detection, such as acoustic and vibration techniques [1,2], radio-frequency identification (RFID)/sensor techniques [3], infrared thermography [4], magnetic flux leakage method [5,6], eddy current technique [7,8], as well as ground penetrating radar (GPR) [9,10,11]. Among these non-destructive techniques, GPR is widely used because it can locate both non-metallic and metallic objects without prior knowledge.…”
Section: Introductionmentioning
confidence: 99%